Designing for Reflection - Kun, Peter (My University, 2013)
Researching designing for reflection has been a niche interest of few interaction designers in the past. Reflection, as an individual and informal mental activity is a complicated experience to design for, and no appropriate design method has so far been developed. The thesis summarize the main views on reflection, and the history of reflection in interaction design. Afterwards, the Reflection Design Method is introduced, which can potentially be used during the design process to imbue a design with qualities that motivate reflection. The method consists of two parts: (a) a guiding framework for designers to expand their design processes by providing guidance how to introduce reflective qualities into conceptual designs; (b) a collection of reflective design patterns, which help designers to look for inspiration in their own ideation processes. The nal outcome was reached by following a research through design approach. The starting point of the process was an investigation of earlier studies on reflection, based on which a preliminary framework was created. This framework was then complemented with the outcomes of a qualitative questionnaire, resulting in the first version of the Reflection Design Method. The next iterations of the method integrated the user feedback and the observations from two conducted workshops, and the nal iteration was concluded with an expert review. The Reflection Design Method provides an applied approach to help designers to tackle this otherwise abstract area. The design method can potentially provide alternatives for other, similar design focus areas, such as designing for sustainability or behavioral change.
Keywords: Interaktionsteknik; Interaction Technologies